THE USAGE OF ANATOMAGE AND PLASTINATION IN ANATOMY LEARNING: STUDENT PERCEPTIONS AND LEARNING OUTCOMES - Nurfitri Bustamam; Diana Agustini Purwaningastuti (Asosiasi Institusi Pendidikan Kedokteran Indonesia, 2021)
Background: In the Academic Year 2017/2018 the Faculty of Medicine Universitas Pembangunan Nasional Veteran Jakarta (FMUPNVJ) began using anatomage and plastination as learning tools. This study aims to describe the learning process, compare learning outcomes of students after using anatomage and plastination with the learning outcomes of students in the previous academic year, and describe students’ perceptions regarding the learning tools used.Methods: A cross-sectional study was conducted on the population of second-semester FMUPNVJ students who had taken dermatomusculoskeletal (DMS) block in the academic year 2017/2018. Data were taken from the total population (n = 163). A questionnaire with a 5-point Likert scale and open-ended questions were used to obtain student perceptions related to the learning process and the learning tools used. Semester grade point average (GPA) before taking the DMS block and results of anatomy practical exam of the subjects (n = 163) and students of the previous academic year (n = 157) were analyzed.Results: The students appreciate learning using anatomage and plastination. The Mann-Whitney test result showed that there was no difference in semester GPA before taking DMS block between the two groups (p = 0.090). However, the learning outcomes after using anatomage and plastination were lower than those using only cadaver and mannequin (p = 0.002). Each learning tool has some advantages and disadvantages. Conclusion: The usage of anatomage and plastination at Anatomy Laboratory FMUPNVJ has not been able to improve learning outcomes. Anatomage features need to be used optimally to enhance the learning outcomes.